High Intra-Abdominal Pressure Secondary to Obesity as a Determining Factor for Ventriculoperitoneal Shunt Malfunction - Morais, Barbara Albuquerque; Yamaki, Vitor Nagai; Cardeal, Daniel Dante; Andrade, Fernanda Goncalves; Paiva, Wellingson Silva; Matushita, Hamilton; Teixeira, Manoel Jacobsen (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
The ventriculoperitoneal shunt (VPS) is an established treatment for hydrocephalus. The functioning of the system requires a pressure difference between the cranial and abdominal cavities. The VPS can be particularly problematic in patients with increased intra-abdominal pressure (IAP). We report the case of a 16-year-old girl with VPS since she was 2 months old due to hydrocephalus secondary to myelomeningocele. The patient had been asymptomatic ever since, but she sought the emergency service with intermittent headache and vomiting. A non-enhanced brain tomography, a shunt trajectory X-ray and an abdominal ultrasound revealed no cause of system malfunction. In view of the persistent clinical picture, a revision of the shunt was performed, which revealed adequate intraoperative functioning. She returned with the same symptoms two weeks after surgery. The patient was obese (body mass index [BMI]: 48). We hypothesized intermittent valve malfunction due to increased intra-abdominal pressure. She underwent a ventriculoatrial shunt, without intercurrences. In the postoperative period, the patient presented transient tachycardia and was asymptomatic at the 6-month follow-up. Obesity should be considered an important variable for the inadequate functioning of the VPS due to increased IAP and catheter dystocia to the extraperitoneal cavity. Studies have already correlated the IAP with the BMI, which reaches between 8 mm Hg and 12 mm Hg in obese individuals. Therefore, the BMI can be considered during the selection of valve pressure in systems with non-adjustable valves to prevent insufficient drainage. The recognition of obesity as a cause of VPS malfunction is fundamental to avoid unnecessary surgeries and intermittent malfunction of the system.
Keywords: obesity; ventriculoperitoneal shunt malfunction; hydrocephalus; intra-abdominal pressure